Математичне моделювання вібраційної касетної установки для формування залізобетонних виробів - Нестеренко, М. П. (Техніка будівництва, 2020)
The description of the design and operating principle of vibrating cluster installation of horizontal directional vibrations to create small products using plug vertical partitions to separate forms in separate compartments. The process of interaction between the vertical sides cluster installation of a concrete mixture. Defined physical and mechanical properties of the concrete mix, which vrahuvuyut elastic and inelastic resistance forces and inertial forces concrete. Analytical dependence for determining the law of motion of vertical walls in the form of plug plates and longitudinal sides cluster forms